Clinical presentation and risk factors of serious infections in children with Down syndrome treated for acute lymphoblastic leukemia. Issue 11 (11th July 2016) - Ceppi, Francesco; Stephens, Derek; den Hollander, Barbara S.; Krueger, Joerg; Whitlock, James; Sung, Lillian; Hitzler, Johann
Abstract: Background: Treatment of acute lymphoblastic leukemia (ALL) in children with Down syndrome (DS) is associated with a higher incidence of life‐threatening infections compared to the overall pediatric population. The objective of this study was to describe infections and identify risk factors of microbiologically documented infections at a sterile site in children with DS during chemotherapy for ALL. Procedure: We conducted a single‐institution retrospective review of infectious episodes encountered by patients with DS during primary treatment for ALL. Correlations between features of clinical presentation and severity of microbiologically proven infections were investigated. Results: Among 237 suspected infectious episodes encountered by 35 patients with DS and ALL (DS–ALL), a total of 40 episodes (16.9%) had the clinical presentation of a severe infection (SI). Seventeen patients had 33 (13.9%) microbiologically proven infections from a sterile site. Fever was not part of the clinical presentation in 27% of microbiologically documented infectious episodes. The odds ratio of a microbiologically proven infection at a sterile site was significantly increased during a 7‐day interval after treatment with glucocorticoids (2.18; 95% CI: 1.02–4.66; P = 0.04). Neither administration of anthracyclines in the preceding 14 days nor neutropenia correlated with infections. Conclusions: Serious infections in DS–ALL may present without typical signs such as fever. The immediate time period following administration of glucocorticoids is particularly associated with the risk of SIs.